A Comparative Analysis of Expert Advisors' Role Perceptions in Policymaking: The Case of Hong Kong, China. Issue 5 (2nd September 2020) - Li, Wei
Abstract: Using the Q method with a Hong Kong dataset, this paper identifies four types of expert advisors in a hybrid regime. These four types have shared and distinct preferences for managing tensions between scientific knowledge and value/interests, between scientific and layperson' knowledge, and the different preferences of policymakers, citizens, and experts. Their degrees of involvement in policymaking and varied strategies to influence policymaking reflect the features of the hybrid regime. The findings provide useful lessons for expert advisors to manage tensions between science and politics over contested issues.